Crimillegal Orders: Revisiting Organized Crime’s Political Power - Markus Schultze-Kraft (Íconos)
Despite its relevance to understanding political change and instability in many parts of the global South, the relationship between organized crime and political order remains understudied. This article introduces the novel concept of “crimillegality” to address this issue. Taking recourse to the conceptions of political order put forward by Weber, Fukuyama and North, Wallis and Weingast, I explain how regular patterns of social exchange and interaction - involving public and private, and state and non-state actors - that span an assumed divide between the realms of legality (“legitimate upper world”) and criminality (“illegitimate underworld”) influence the character, shape and evolution of political order. I suggest that it is in crimillegal orders that organized criminality acquires political power to its fullest and that oligopolies of coercion and violence are constitutive elements of such orders. The article concludes by presenting some ideas about how the concept of crimillegality could be usefully adopted in the fields of peace building and the mitigation of non-armed conflict violence in Latin America and other parts of the contemporary world.